(untitled) - Toynbee, Arnold J. (Royal Institute of International Affairs, 1934)
The inspiration of historians : The historian's angle of vision; the attractiveness of the facts of history, the impulse to investigate the relations between the facts of history, the feeling for the poetry in the facts of history...
Keywords: Civilization,Nền văn minh; History,Lịch sử